The breeding work on the winter bread wheat varieties of intensive type in the FSBSI “Agricultural Research Center “Donskoy” - O. V. Skripka; S. V. Podgorny; A. P. Samofalov; V. L. Chernova (Зерновое хозяйство России)
The systematic study on winter wheat breeding began in 1955 in the former Zernograd experimental station, and now the Federal State Budgetary Scientific Institution “ARC “Donskoy”. Under these conditions, the development of the most suitable for local conditions varieties of intensive type with increased frost resistance determined the main direction of winter wheat breeding in those years. In the early 1980s, the area of black fallow increased in the Rostov region, much attention was paid to irrigated agriculture. There was planned to increase the area under irrigation in the North Caucasus to 1 million hectares. Therefore, there was set a goal to develop highly productive, low-stemmed, resistant to lodging varieties, responsive to mineral fertilizing with complex immunity to diseases. The breeding work of the laboratory for the breeding and seed production of winter bread wheat of an intensive type over the past forty years resulted in the development of 22 varieties of intensive type with good adaptability to the conditions of the Rostov region. In 2020, 17 winter bread wheat varieties of an intensive type were included into the State List of Breeding Achievements, five varieties ‘Yubiley Dona’, ‘Zodiak’, ‘Univer’, ‘Razdolye’, ‘Rubin Dona’ are currently undergoing the State Variety Testing at the SVTs of the Russian Federation. A stable productivity improvement is possible only with the emphasis on the development of varieties with broad adaptive properties, providing sufficiently high yields under various cultivation conditions. Among the breeding traits that affect productivity stability, the most significant in the conditions of the Don are winter and frost resistance, disease resistance, drought resistance, early ripeness, and grain quality. Therefore, the adaptive potential increase is the most important task for the future breeding. In order to solve this problem, intraspecific and interspecific hybridization, followed by targeted selection, remains the main breeding method of winter bread wheat of an intensive type.